Amino acid profile and chemical characteristics by-product process wet rendering of fish lele (Clarias Sp.) and tuna (Euthynnus Spp.) - Minarny Gobel; Jusri Nilawati; Prisma Wiryanti; Roni Hermawan; Muhamad Musbah (Depik, 2024)
This study was conducted to determine the amino acids profile and chemicals content (moisture content, protein, and fat) catfish and tuna products. Wet rendering process, each sample is steamed at 1500C for 30 minutes, after the sample is pressed with the aim of removing fluid from the fish's body. The liquid is centrifuged to separate the layers of oil and air. After obtaining fish oil, the byproducts are liquid / broth and solids (fish dregs). The byproducts (fish pulp and broth) were analyzed for amino acid profiles using High Performance Liquid Chromatography (HPLC) (AOAC, 2005) Chemical characteristics (air content, protein, fat) were analyzed using the AOAC (2005). The results showed that glutamic acid was higher in tuna pulp which was 11.83% and catfish 8.85%, while tuna broth contained amino acid histidine which was quite high at 10.49%, and 11.53% glycine in fish broth catfish. Furthermore, the levels of pulp and fish stock are 12.63% and 78.28% respectively, catfish 11.58%; and 83.45%. The fat content of catfish is higher that is 1.84% and 3.26% compared to tuna which is 1.57% and 2.74% tuna protein is 81.16% higher than catfish which is 75.46%, but the protein content of tuna broth is 56.84% lower than that of catfish broth which is 69.16%.Keywords: amino acid profiletuna fishcatfishwet renderingby-product